Is the Value Added Tax Naturally Progressive? - Glenn P. Jenkins; Hatice Jenkins; Chun-Yan Kuo (Queen's University, Department of Economics, 2006)
A broad based consumption tax, such as a value added tax, is generally considered to be a regressive tax. This conclusion, however, has not taken into account the fact that in developing countries the commodities on which poor households spend most of their income, even if they are included in the legal tax base, are administratively impractical to tax. This paper employs a rich data set on household incomes and expenditures for the Dominican Republic. The data set covers 2042 goods and services purchased by households of different income and consumption levels. It also contains information on the type of establishment from which the items were purchased. With this information, we estimate the effective rate of tax that has been paid on each item purchased by households. These estimations include the effect of the different rates of the tax compliance across households with different expenditure levels. The results of the study show that the burden of the current VAT in the Dominican Republic is progressive over all the quintiles of household expenditure. Furthermore, if the base of the VAT is made comprehensive, the estimated incidence of the burden of the VAT is still progressive over all the quintiles of household expenditure.
Keywords: H22; H26; 330; Value Added Tax; incidence; compliance